Institutional Quality, Bilateral Trade and Global Value Chains in Africa - Alhassan, Abdulkareem (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
The importance of trade and institutions as drivers of economic growth and development has been established in both theoretical and empirical literature. Moreover, global value chains (GVC) propels substantial expansion in international trade across the globe over the last two decades. However, the institutions-GVC link and institutions-bilateral trade nexus in Africa suffers complete neglect in international trade research. This is despite the dismal performance of the continent in institutional quality, bilateral trade and GVC participation. Therefore, this thesis evaluates the effect of institutional quality on bilateral trade and GVC participation in Africa. In the first part, Poisson Pseudo Maximum Likelihood with High-Dimensional Fixed Effects estimator (PPMLHDFE) is applied to estimate Structural Gravity Model for the evaluation of the impact of both political and economic institutions on bilateral exports, imports and aggregate trade. A sample of 37 Sub-Sahara African countries with 124 of their trading partners for the period 2000-2018 was used for the analysis. The second part investigates the impact of institutions on backward, forward and total GVC participation as well as GVC position (upstreamness) in Africa using system-GMM estimator for a sample of 47 African countries over the period 2000-2018. The findings reveal that both political and economic institutions are significant determinants of bilateral trade and GVC participation in Africa. However, the popular submission of previous studies that institutions generally have positive impact on international trade does not apply in this case. The effects of the institutional factors are heterogeneous depending on the components of institutional quality, bilateral trade, GVC participation and income groups of the countries. Thus, this thesis offers appropriate policy recommendations on the appropriate institutional framework to adopt for the improvement of bilateral trade and GVC participation in the continent. Keywords: Institutional quality, bilateral trade, global value chains, Africa.

ÖZ: Dış ticaretin ve kurumların ekonomik büyüme ve kalkınma üzerindeki etkisi hem teorik hem uygulamalı çalışmalarda geçerliliği kanıtlanmış bir olgudur. Öte yandan, son yirmi yılda küresel değer zincirleride (KDZ) küresel dış ticaret hacminin genişlemesinde önemli katkıda bulunmuştur. Bununla beraber, kurumsal yapıların KDZ ile olan etkileşimi ve ikili ticaretle olan bağlantıları konusunda özellikle Afrika ülkelerini kapsayan çalışmalar uluslararası dış ticaret araştırmalarında yer almamıştır. Bölge ülkelerinin kurumsal kalitelerinin tatminkar olmaktan uzak olmaları, ikili ticaret ilişkilerinin ve KDZ katılım oranlarının düşük seviyede seyretmesi bile kıtayla ilgili çalışmaları motive etmekte çok yetersiz kalmıştır. Bu tez çalışmasının ana amacı Afrika ülkelerinin kurumsal kalite faktörlerinin ikili ticaret ve KDZ katılımına olan etkilerini inceleyerek bu alandaki boşluğu doldurmaktır. Mevcut tez çalışmasının ilk bölümünde Afrika ülkelerinin siyasi ve ekonomik kurumlarının ikili dış ticaret ilişkileri, ihracat , ithalat ve KDZ katılımı üzerindeki etkileri, çok-boyutlu sabit etkileri de içeren yeni PPMLHDFE tahmin metoduyla Yapısal Çekim Modeli çerçevesinde tahmin edilmektedir. Çalışmada 37 Sahra-Altı Afrika ülkesinin 2000-2018 döneminde ticaret yaptığı 124 ülkeyle olan ticaret verileri kullanılmıştır. Çalışmanın ikinci bölümünde 47 Afrika ülkesinin 2000-2018 dönemine ait verileri kullanılarak, kurumların ileri ve geriye dönük ve toplam katma değer katılımları ve KDZ pozisyonları (üst zincir) üzerindeki etkileri Genelleştirilmiş Momentler Yöntemi (GMM) tahmin yöntemiyle incelenmektedir. Bulgular siyasi ve ekonomik kurumların karşılıklı ticaret ve KDZ katılımı üzerinde önemli etkileri olduğuna işaret etmektedir. Öte yandan genel olarak kurumların dış ticarete olan etkilerinin daima olumlu yönde olduğu görüşü doğrulanmamıştır. Kullanılan kurumsal kalite faktörünün özelliğine, KDZ katılım oranına ve ülkelerin gelir düzeyine göre kurumsal faktörlerin etkileri değişkenlik arzetmektedir. Çalışmada bu durum gözönüne alınarak ikili dış ticaret ilişkilerinin gelişmesi ve KDZ katılım oranlarının artırılması için uygun kurumsal çerçevenin oluşturulmasına yönelik politika önerileri yeralmaktadır. Anahtar Kelimeler: Kurumsal kalite, ikili ticaret, küresel değer zincirleri, Afrika.
Doctor of Philosophy in Economics. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2021. Supervisor: Prof. Dr. Cem Eşref Payaslıoğlu
Keywords: Economics; Economics--Africa; Business Networks--Africa; International trade--International economic relations; Economic Conditions and Development--Africa; Business enterprises; Globalization--Economic aspects--Africa; Institutional quality; bilateral trade; global value chains; Africa